2012
DOI: 10.1088/0953-8984/24/49/495901
|View full text |Cite
|
Sign up to set email alerts
|

The extrinsic origin of the magnetodielectric effect in the double perovskite La2NiMnO6

Abstract: A La(2)NiMnO(6) polycrystalline sample prepared by the sol-gel method showed monoclinic crystal structure with the P2(1)/n space group and a saturation magnetization of 4.63 μ(B)/f.u. at 5 K. Impedance spectroscopy results in the temperature range of 10 K < T < 300 K have revealed a distinct conduction process at grains and grain boundaries, where the grains followed the variable range hopping mechanism and the grain boundaries obeyed Arrhenius thermal activation. A negative magnetoresistance of 2.5% was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 39 publications
7
70
0
Order By: Relevance
“…Fig. 7 (b) presents the Arrhenius plot of the dc-conductivity of the Sm 2 NiMnO 6 ceramics, for which an activation energy of about ∼0.17eV was determined by linear regression analysis The activation energy for Sm 2 NiMnO 6 double perovskite ceramics is comparable with the activation energy of ∼0.14eV calculated from the dc-conductivity for Ho 2 NiTiO 6 perovskites reported by Mahato et al [30] or with the activation energies reported by Chandrasekhar et al [31] for La 2 NiMnO 6 double perovskites (values around M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 0.14eV and 0.119eV corresponding to the grain and grain boundary, respectively). Activation energies of about 0.17 eV were also reported for La 2 NiMnO 6 double perovskites [15].…”
Section: A N U S C R I P Tsupporting
confidence: 77%
“…Fig. 7 (b) presents the Arrhenius plot of the dc-conductivity of the Sm 2 NiMnO 6 ceramics, for which an activation energy of about ∼0.17eV was determined by linear regression analysis The activation energy for Sm 2 NiMnO 6 double perovskite ceramics is comparable with the activation energy of ∼0.14eV calculated from the dc-conductivity for Ho 2 NiTiO 6 perovskites reported by Mahato et al [30] or with the activation energies reported by Chandrasekhar et al [31] for La 2 NiMnO 6 double perovskites (values around M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 0.14eV and 0.119eV corresponding to the grain and grain boundary, respectively). Activation energies of about 0.17 eV were also reported for La 2 NiMnO 6 double perovskites [15].…”
Section: A N U S C R I P Tsupporting
confidence: 77%
“…Multifunctional double perovskite oxides (DPOs) Ln 2 NiMnO 6 [Ln = lanthanides] have gained immense research interest in the recent years due to their rich physical properties which make them as the prospective materials for technological applications [1][2][3][4][5][6][7][8][9][10][11][12]. In this family La 2 NiMnO 6 having ferromagnetic order temperature of about 280 K is a rare example of a single material platform with multiple functions, in which the spins, electric charges, and dielectric properties can be tuned by magnetic and/or electric fields.…”
Section: Introductionmentioning
confidence: 99%
“…al [4]. These properties make this series of materials suitable for possible applications in spintronic devices, such as magnetic memories and magnetodielectric capacitors [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…Nickel precipitates, primarily as LaNiO 3 or La 2 NiO 4 , have been reported, but perhaps the most interesting is an amorphous form of La 2 O 3 , proposed as a sink for lanthanum to create vacancies in the perovskite but for which no direct information from X-ray diffraction (XRD) or other methods of analysis has yet been obtained. La 2 NiMnO 6 samples have been synthesized in single crystal [12], polycrystalline [4,13,14], nanoparticle [15,16] and thin film [4,[17][18][19][20] forms by a variety of methods. Despite their complicated and defect-prone nature, the composition and stability of the La 2 NiMnO 6 surface have received little attention.…”
Section: Introductionmentioning
confidence: 99%